Sex Determination in Male and Female Melopsittacus undulates using a Morphometric Method - Baehaqi, Ibnu; Saraswati, Tyas Rini; Yuniwarti, Enny Yusuf Wachidah (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Parakeets (Melopsittacus undulates) are classified parrot order Psittaciformes. Parakeets are monomorphic birds whose sex is difficult to be distinguished. Sex identification is very important for breeding efforts in order to increase the parakeet population. External morphology was determined to identify the sex of the birds. This research was conducted to determine the sex of parakeets (male and female). This study used five male and five female parakeets aged 4 months as the study objects. This study used the quantitative and qualitative method. Results of this study was verified by performing surgery to determine the sex of parakeet based on their reproductive organs. The t-test results of morphometric characteristics showed no significant different in the length of body, upper bill, lower bill, wing, tail, femur, tibial-tarsus, tarsometatarsus and digits as well as the body weight between male and female parakeets. The color of the cere was useful to accurately determine sex in parakeets (blue in males and white in females). This research provided information to the public about the differences between male and female parakeets for the selection of good broodstock in order to increase their population in captivity.